Granulysin-high decidual NK cells in macaques and humans share signatures of immune defense - Nina Salinger Prasanphanich; Giulia Protti; Monica Cappelletti; Feiyang Ma; Neema Pithia; Angel Dasenbrock; Jerzy Stanek; Claire A. Chougnet; Suhas G. Kallapur; Matteo Pellegrini; Tamara Tilburgs; Pietro Presicce (Cell Reports, 2025)
Summary: Decidual natural killer cells (dNKs) are key immune effector cells at the maternal-fetal interface. dNKs utilize the antimicrobial peptide granulysin (GNLY) to kill bacteria without killing infected trophoblasts. Since rodents lack the GNLY gene, the in vivo biology of GNLY expression by dNKs and their role during intra-uterine infection (IUI) is not well understood. Here, we defined dNK GNLY expression in placental membranes in a rhesus macaque model of IUI and compared it with human acute chorioamnionitis (ACA). GNLY-high dNKs of both species shared conserved transcriptional and protein signatures of antimicrobial defense and immunoregulation. Moreover, GNLY-high dNKs responded to inflammation and infection by increasing their cytotoxic, cytokine, and inflammatory signatures. Thus, high GNLY expression defines a unique dNK type with active roles in immune defense. Defining the regulatory networks of GNLY expression by dNKs and their unique mechanisms of infection control will generate therapeutic opportunities to enhance immunity and reduce IUI-related pregnancy complications.